2013
DOI: 10.1176/appi.ps.002092012
|View full text |Cite
|
Sign up to set email alerts
|

The Mindfulness-Based Psychoeducation Program for Chinese Patients With Schizophrenia

Abstract: The findings provide evidence that the mindfulness-based education program can improve Chinese schizophrenia sufferers' psychosocial functioning and reduce their illness relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 13 publications
2
83
1
2
Order By: Relevance
“…About 1,250 records were removed after screening the relevance of article titles and abstracts to the topic of the review. The full texts of the remaining 21 studies were reviewed and finally 15 studies were excluded after full review, leaving behind only six studies [17][18][19][20][21][22] to be included for this review. Details of the searching process are shown in Figure 1.…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…About 1,250 records were removed after screening the relevance of article titles and abstracts to the topic of the review. The full texts of the remaining 21 studies were reviewed and finally 15 studies were excluded after full review, leaving behind only six studies [17][18][19][20][21][22] to be included for this review. Details of the searching process are shown in Figure 1.…”
Section: Study Selectionmentioning
confidence: 99%
“…In the six randomized controlled studies, two were pre-and post-test design 20,21 and the other studies (n= 4) [17][18][19]22 used repeated-measures design with varying follow-up periods from 6 months 17 to 2 years 22 .…”
Section: Design Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Langer et al (2012) found that no significant effects were observed in any measure between the groups, except in mindfulness response to stressful thoughts and images within the Mindfulness-Based Cognitive Therapy group (eight individual sessions). Chien and Lee (2013) found that Mindfulness-based Psychoeducation (MBP-12 group sessions) was associated with significant change in symptom sever-ity, illness insight, and length of re-hospitalisation at post-intervention, while functioning and number of re-hospitalisations improved significantly only at the 18-month follow-up. Chien and Thompson (2014) found that MBP was associated with greater improvement in insight and treatment attitudes, functioning, psychiatric symptoms, and duration of hospital readmissions.…”
Section: Mindfulness-based Interventionsmentioning
confidence: 99%